2015
DOI: 10.1080/19476337.2014.996916
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of acephate, ethoprophos, and monocrotophos in CHO-K1 cells

Abstract: This work evaluates the cytotoxicity of acephate, ethoprophos, and monocrotophos in the Chinese hamster ovary cell line. The neutral red incorporation (NRI), total cellular protein (TCP) content, and methyl tetrazolium (MTT) assays were followed to estimate the midpoint cytotoxicity values, NRI 50 , TCP 50, and MTT 50 , respectively. The targeted cells were exposed to the tested pesticides in the presence and absence of fetal calf serum. The effects of the sublethal concentration (NRI 25 ) on glutathione S-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Cell viability testing revealed that degraded products were less toxic than non-degraded monocrotophos. Another screening of the MTT assay was carried out by Al-Sarar et al (2015) [51] on the CHO-K1 cell line for which after 24 h of incubation, an MTT50 value of 113.52 ± 10.65 was obtained for monocrotophos in serum-free media. Another genotoxicity study was carried out on lymphocytes of Rattus norvegicus through comet and micronucleus assay showed the toxic effect of monocrotophos through generation of single-and double-strand breaks in DNA and micronucleus in mono and polychromatic erythrocytes [52].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Cell viability testing revealed that degraded products were less toxic than non-degraded monocrotophos. Another screening of the MTT assay was carried out by Al-Sarar et al (2015) [51] on the CHO-K1 cell line for which after 24 h of incubation, an MTT50 value of 113.52 ± 10.65 was obtained for monocrotophos in serum-free media. Another genotoxicity study was carried out on lymphocytes of Rattus norvegicus through comet and micronucleus assay showed the toxic effect of monocrotophos through generation of single-and double-strand breaks in DNA and micronucleus in mono and polychromatic erythrocytes [52].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%